COVID-19 inactivated booster vaccines elicit strong protection against SARS-CoV-2 wild-type and Omicron variant in patients with breast cancer - Li, Xiaomeng; Xu, Yali; Li, Haolong; Li, Linrong; Liu, Yongmei; Zhan, Haoting; Sun, Qiang; Li, Yongzhe (Frontiers in Medicine, 2025)
BackgroundPatients with breast cancer are at an increased risk of severe COVID-19 and related mortality. However, the ability of inactivated vaccine-induced antibodies to neutralize both SARS-CoV-2 and its Omicron variant following a third SARS-CoV-2 vaccine dose remains unclear in these patients.MethodsBlood samples from 211 breast cancer patients and 155 healthy controls were analyzed after one, two, or three doses of the inactivated SARS-CoV-2 vaccine. Levels of total anti-SARS-CoV-2 antibodies, anti-receptor binding domain (RBD) IgG, and neutralizing antibodies (NAbs) against both the SARS-CoV-2 wild-type virus and the BA.4/BA.5 (Omicron) variant, along with lymphocyte subsets, were measured 2 weeks to 3 months and more than 6 months after the second and third vaccinations, respectively.ResultsLevels of anti-RBD IgG and NAb inhibition rates against both the SARS-CoV-2 wild-type virus and the BA.4/BA.5 (Omicron) variant were significantly higher in breast cancer patients after the third dose than after the second dose. However, these levels remained lower than those observed in healthy controls. Univariate analysis revealed that >6 months after receiving two or three doses was associated with undetectable NAbs against the SARS-CoV-2 wild-type virus compared to those at 2 weeks to 3 months. Additionally, patients aged 60 years or older were correlated with undetectable NAbs against the BA.4/BA.5 (Omicron) variant. Immune responses after two or three doses were not affected by endocrine therapy, either current therapy or vaccination. In particular, univariate and multivariate analyses revealed that the vaccination of breast cancer patients with CoronaVac resulted in significantly higher NAb inhibition rates against the SARS-CoV-2 wild-type virus than BBIBP-CorV.ConclusionBreast cancer patients boosted with a third dose of inactivated vaccines demonstrated the potent neutralization of SARS-CoV-2 and the Omicron variant compared to receiving one or two doses. Vaccination-mediated NAb induction was affected by age, time > 6 months after vaccination, vaccine type, and cancer-targeted treatment. Therefore, the study results indicated an urgent need for caution and additional strategies to protect these patients.